RELIGIOUS PLURALISM IN LABUHAN PARANGKUSUMO TRADITION: COMMUNICATING LOCAL JAVANESE WISDOM AND THE MORAL MESSAGE OF THE QUR’AN - Nuzulanisa, Kafhaya; Fariha, Zidna (Universitas Nurul Jadid, 2022)
This article discusses the religious pluralism contained in the procession of the Labuhan Parangkusumo tradition. The problem underlying this study is that Indonesia, rich in culture, tradition, and religion, is prone to conflict and violence due to a lack of public understanding of the value of pluralism. This study used the living Qur'an approach with a descriptive-qualitative method. Data collection techniques were obtained from informants conveying the Labuhan Parangkusumo tradition as primary data and supported by some secondary data in the form of literature and sources from other media related to the Labuhan Parangkusumo tradition. In the end, this research shows a form of religious pluralism in the traditional harbor prayer procession that involves all religions. As well as there are signs of religious pluralism in QS. Al-Kafirun (109): 6, which talks about religious tolerance